Pay for performance: compensation reforms - Jamaiudin, Norhaslinda (Routledge Taylor and Francis Group, 2013)
This chapter examines the development of pay for performance in the Malaysian public sector, and its implementation. The discussion is divided into three sections. It begins with a brief overview of the historical development of pay policies. The second section discusses the pay for performance practice, highlighting the salient features of the NRS and MRS. The final section shows some of the problems and challenges encountered in the implementation of new pay policies.